2015
DOI: 10.1128/iai.00171-15
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Virus-Bacterium Interactions in a Porcine Precision-Cut Lung Slice Coinfection Model: Swine Influenza Virus Paves the Way for Streptococcus suis Infection in a Two-Step Process

Abstract: Swine influenza virus (SIV) and Streptococcus suis are common pathogens of the respiratory tract in pigs, with both being associated with pneumonia. The interactions of both pathogens and their contribution to copathogenesis are only poorly understood. In the present study, we established a porcine precision-cut lung slice (PCLS) coinfection model and analyzed the effects of a primary SIV infection on secondary infection by S. suis at different time points. We found that SIV promoted adherence, colonization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 46 publications
5
89
0
2
Order By: Relevance
“…This result is most likely due to the presence of sialic acid on the capsular polysaccharide of wt strain 10 and the 10Δsly mutant. Recent studies have shown that the sialic acid binding activities of influenza viruses recognize the capsular sialic acid of S. suis, resulting in bacterial adherence to influenza virus-infected cells (6,10,19,20). The 10Δsly mutant is encapsulated and, therefore, can benefit from this adherence mechanism, too.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is most likely due to the presence of sialic acid on the capsular polysaccharide of wt strain 10 and the 10Δsly mutant. Recent studies have shown that the sialic acid binding activities of influenza viruses recognize the capsular sialic acid of S. suis, resulting in bacterial adherence to influenza virus-infected cells (6,10,19,20). The 10Δsly mutant is encapsulated and, therefore, can benefit from this adherence mechanism, too.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza virus infections may cause increased susceptibility to secondary bacterial pneumonia, resulting in increased morbidity and mortality rates in the human population; the mechanisms underlying this copathogenesis are not well understood (13,14). For S. suis, it has been shown that the interaction of influenza A virus hemagglutinins with capsular sialic acids results in the binding of streptococci to virus-infected cells (6,19,20). This adherence mechanism is more efficient than the binding mediated by bacterial adhesins (6,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, all of the samples were stored at 4°C until examination under a Nikon Eclipse Ti-S inverse immunofluorescence microscope equipped with a 10ϫ/0.30 Plan Fluor objective (Nikon). Subsequently, the area of the NPTr cells surface positive for red fluorescent HA protein was analyzed by applying analySIS 3.2 software (Soft Imaging System) to quantify HA attachment (73).…”
Section: Methodsmentioning
confidence: 99%